Good and not-so-good practices in creative tourism networks and platforms: an international review - Remoaldo, Paula (2019)
A consensus has not yet been reached worldwide regarding the concept of creative tourism. Since 2000, it has generally been considered as a kind of tourism that can offer tourists the opportunity to co-create and develop their creative potential. To identify and analyze the nature of existing creative tourism practices today, we carried out an investigation to examine creative tourism networks and platforms internationally - providing a snapshop of the creative tourism field in 2017. In this chapter, we outline the difficulties in defining creative tourism and discuss the development of creative tourism spaces on an international scale through the creation of networks and platforms. The chapter provides an overview of the research findings and comments on the patterns, issues, and trajectories we perceived. At the end of the chapter, we provide a summary of future research directions. This research was conducted as part of the CREATOUR (Creative Tourism Destination Development in Small Cities and Rural Areas) project. CREATOUR is developing an integrated approach to creative tourism by combining interdisciplinary, methodological, technical, and theoretical approaches to link the tourism and cultural/creative sectors in non-metropolitan areas of mainland Portugal. The project aims to promote a more sustainable and holistic development of rural and small city/town destinations with a strong historical and cultural past through the active and creative involvement of visitors and residents with local habits, traditions, and customs. The initiatives that are integrated within this project link creative, culture-based activities with various aspects of the 'authentic heritage" of the varied landscape of the country for the benefit of both local residents and participating visitors.